Influence of metal nanocoatings on the corrosion resistance of welded joints of wind power facilities - Poberezhnyi, Liubomyr; Kessler, Sylvia (Frontiers in Materials, 2025)
The construction of numerous offshore wind power plants across the European Union and globally has exposed these structures to corrosive marine environments, leading to significant corrosion damage, particularly in welded joints. This study examines the effect of nickel and nickel-copper nanolaminates on corrosion resistance. Electrochemical methods, including polarization measurements and electrochemical impedance spectroscopy (EIS), were used to evaluate corrosion behavior in tap water and 3.5% NaCl solution. Visual inspection by optical microscopy was performed to analyze localized corrosion defects. BM-Ni and BM-Ni-Cu specimens exhibited galvanic corrosion, more intense in NaCl solution. BM-Ni-Cu samples showed significant potential differences, indicating electrochemical interactions between nanolayers. Corrosion defects initiated at surface imperfections, potentially affecting the integrity of welded joints over time. Surface defects in nanolaminates may serve as corrosion initiation points. The results showed the promising potential of metal multilayer nanocoatings for improving the corrosion resistance of welded joints. Future research should optimize layer thickness and other parameters to improve corrosion resistance and enhance the durability of offshore wind turbines.